Quantitative Risk Assessment (QRA) Prenatal Mercury Exposure of Whitening Cosmetic and Infant Neurodevelopmental Risk - Hasriwiani Habo Abbas; Yuliati Yuliati; Masayuki Sakibara (Journal of Public Health and Pharmacy, 2025)
ntroduction: Mercury compounds are divided into elemental mercury, inorganic mercury, and organic mercury. Exposure to mercury through both direct and indirect pathways can have serious impacts on environmental and health issues, especially sensitive populations such as pregnant women, infants, and children. According to the Global Nielsen institution, 45% of women in Indonesia use whitening cosmetics. It should be noted that the content of whitening cosmetics contains mercury and its derivatives. Pregnant women are exposed to mercury through the use of cosmetics and the consumption of seafood. The impact caused if accumulated in the placenta will cause neonatal neurodevelopmental risk. This study aimed to analysed the quantitative risk assessment of prenatal mercury exposure and neurodevelopmental risk.